Pasting of two diffusion processes on a line with nonlocal boundary conditions - Kononchuk, P. (Інститут математики НАН України, 2008)
In this paper, we obtain an integral representation of an operator semigroup that describes the Feller process on a line that is a result of pasting together two diffusion processes with a nonlocal condition of conjugation.